Scope for Study of Food Habits of Wild Life in India - Chaudhuri, A. B. (Indian Forester, 1966)
The author discusses that the study of food habit of wild life in India is new and practically no detailed information is available. He briefly outlines the scope of such study and the methods that could be adopted for study of various items of food. Evergreen forests of India have wide varieties of plant species whose different parts are edible to wild life species. The author stresses that it is a difficult job for which one should have thorough knowledge of systematics of plants and insects, but foresters definitely are best suited for such job. They only need a small laboratory. The main handicap in India will be availability of enough wild life specimen for study of stomach contents for which it is suggested that observation rather than dissection will form major part of such study in the initial stages.